Changing indications for intravitreal anti-vascular endothelial growth factor injections at the university college hospital, Ibadan, Sub-Saharan Africa - Adewole, Adeyemi Timothy; Oluleye, Tunji Sunday; Babalola, Yewande Olubunmi; Majekodunmi, Oluwole; Ijaduola, Modupe (International Journal of Research in Medical Sciences, 2020)
Background: To review the current indications for intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy, in order to make recommendations for planning of services. Methods: The medical records of 172 patients who had intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections from January 2016 to December 2019 were retrieved. Socio-demographic and clinical data were extracted, analysed, and compared with data from the previously published audit report covering 2010 to 2012. Results: Three hundred and thirty injections were given to 182 eyes in this cohort of patients. The mean age was 61.1±16.3 years (range <1-90 years), with a male to female ratio of 1.1:1. Retinal vein occlusion, 64 (35%) remained the most common indication for anti-VEGF injections in the eyes treated. This was followed by choroidal neovascular membrane/wet age-related macular degeneration which accounted for 42 (23%) as reported previously. However, cases of proliferative diabetic retinopathy/ diabetic maculopathy needing anti-VEGF were noticed to have almost doubled from about 8 (10%) in the previous study to 15 (27%) in the present study. In addition, idiopathic polypoidal choroidal vasculopathy, 18 (10%) ranked above proliferative sickle cell retinopathy in the present study. Retinopathy of prematurity (ROP), neovascular glaucoma, retinal artery macro-aneurysm and myopic choroidal neovascular membrane were the new emerging indications. Conclusion: There is an expanding indication for anti-VEGF in the management of retinal vascular diseases in the health facility and adequate measures should be put in place for early diagnosis and management. Patients should be counselled on the availability of this treatment option.